2006
DOI: 10.1007/s10461-006-9093-7
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Determinants of Condom Use Among Female Sex Exchangers in East Harlem, NYC: An Event Analysis

Abstract: Recent studies have revealed a variety of contexts involving HIV risk behaviors among women who exchange sex for money or drugs. Event analysis was used to identify the individual, relationship, and contextual factors that contribute to these high-risk sex exchange practices. Analyses were conducted on data obtained from 155 drug-using women who reported details of their most recent sex exchange event with male clients. The majority of sex exchange encounters (78%) involved consistent condom use. In multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…We were also lacking information on the context of sexual behaviors with clients, particularly the extent to which they exchanged sex for drugs rather than money, which has been reported elsewhere (Edlin et al, 1994, Sterk, 1998, Inciardi, 1995, McMahon et al, 2006. However, nearly half of all the FSWs in our study reported that their clients used drugs and one fifth reported sharing needles with clients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We were also lacking information on the context of sexual behaviors with clients, particularly the extent to which they exchanged sex for drugs rather than money, which has been reported elsewhere (Edlin et al, 1994, Sterk, 1998, Inciardi, 1995, McMahon et al, 2006. However, nearly half of all the FSWs in our study reported that their clients used drugs and one fifth reported sharing needles with clients.…”
Section: Discussionmentioning
confidence: 75%
“…Juarez. Although reports vary widely, international literature suggests that 21-80% of female IDUs report ever trading sex for money or drugs (Spittal et al, 2003, Lowndes et al, 2003, Latkin et al, 2003, Kozlov et al, 2006, Benotsch et al, 2004 and 9%-82% of FSWs have ever injected drugs (McMahon et al, 2006, Ward et al, 1993, Vandenhoek et al, 1989, Deren et al, 1997A. Valdez, personal communication, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They have increased likelihood of exposure to HIV because of the social context in which they operate (i.e. drug use, poverty, homelessness), through sexual contact with injection drug users, and through economic dependence on multiple concurrent sexual partners which limits their ability to successfully negotiate condoms [2–9]. Understanding the situations and sexual partner types (e.g., new client, regular/recurring client, drug dealer, pimp, boyfriend/spouse, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the efficacy of condom use promotion programs to reduce STI/HIV incidence among couples, there is a need to understand the factors affecting condom use in this population. Most of the studies conducted to determine factors associated with condom use have been conducted among high risk populations such as female sex workers (Grayman et al, 2005;McMahon, Tortu, Pouget, Hamid, & Neaigus, 2006;Wong, Chan, Koh, & Wee, 2000), illegal drug users (Kwiatkowski, Stober, Booth, & Zhang, 1999;Semple, Patterson, & Grant, 2004;Watkins, Metzger, Woody, & McLellan, 1993), STD clinic attendees (Chatterjee, Hosain, & Williams, 2006;Weinstock, Lindan, Bolan, Kegeles, & Hearst, 1993;Wilson et al, 2004), populations with high sexually transmitted infection (STI) prevalence and HIV-infected women (Clark, Kissinger, Bedimo, Dunn, & Albertin, 1997), and adolescent populations (Anderson, Santelli, & Mugalla, 2003;Orr et al, 1992;Orr & Langefeld, 1993;Pendergrast, Durant, & Gaillard, 1992). In addition, previous studies were mostly cross-sectional in design (Calazans, Araujo, Venturi, & Franca, 2005;Chatterjee et al, 2006;Clark et al, 1997;Hernandez-Giron et al, 1999;Posner, Bull, Ortiz, & Evans, 2004;Weinstock et al, 1993).…”
Section: Introductionmentioning
confidence: 99%